2011
DOI: 10.1371/journal.pone.0015943
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Host Defense against Aspergillus fumigatus Involves Alveolar Macrophages with a Predominance of Alternatively Activated Phenotype

Abstract: The ubiquitous fungus Aspergillus fumigatus is associated with chronic diseases such as invasive pulmonary aspergillosis in immunosuppressed patients and allergic bronchopulmonary aspergillosis (ABPA) in patients with cystic fibrosis or severe asthma. Because of constant exposure to this fungus, it is critical for the host to exercise an immediate and decisive immune response to clear fungal spores to ward off disease. In this study, we observed that rapidly after infection by A. fumigatus, alveolar macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
94
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 70 publications
0
94
2
Order By: Relevance
“…In support, we found that Poly I:C-treated sham-operated animals also demonstrate a decrease in CD11b ϩ CD206 ϩ cells. CD206 is a C-type lectin carbohydrate binding protein expressed by alternatively activated macrophages and associated with recovery and restoration of function (Bhatia et al, 2011). Therefore, our data indicate that poly I:C has a general detrimental effect on "protective" microglia and suggest that, rather than affecting the proinflammatory response, deleterious Poly I:C-mediated effects may instead predominantly downregulate the reparative response.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In support, we found that Poly I:C-treated sham-operated animals also demonstrate a decrease in CD11b ϩ CD206 ϩ cells. CD206 is a C-type lectin carbohydrate binding protein expressed by alternatively activated macrophages and associated with recovery and restoration of function (Bhatia et al, 2011). Therefore, our data indicate that poly I:C has a general detrimental effect on "protective" microglia and suggest that, rather than affecting the proinflammatory response, deleterious Poly I:C-mediated effects may instead predominantly downregulate the reparative response.…”
Section: Discussionmentioning
confidence: 71%
“…Neonatal HI decreases Akt phosphorylation (Brywe et al, 2005) and in turn increases axonal injury (Xiong et al, 2012). Akt phosphorylation plays an important role in the TRIF signaling pathway and promotes cell survival in response to innate immune stimulation (Park et al, 2006;Joung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may help to reconcile conflicting conclusions in the field about the protective roles of macrophages against A. fumigatus. For example, with clodronate liposome-mediated macrophage depletion in mice, Mircescu et al (12) concluded that macrophages are dispensable for inhibiting germination and host survival, while Bhatia et al (37) reported a protective role for macrophages after showing an increased fungal burden in the absence of macrophages. Our findings, from a model completely dependent on innate immune defenses, indicate that macrophages do in fact contribute to host survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that macrophages in the airspace of patients with asthma are functionally different from those from healthy individuals (5,6). In Th2 cytokine-enriched allergic inflammation associated with exposure to parasites or allergen, alternatively activated M2 macrophages are seen in various animal models, although their role remains controversial (7,8). A role for macrophages in the cellular and molecular pathogenesis of Th2 inflammation has not been defined in human disease, and it is still unclear how transformation of the macrophage population in the airspace occurs in response to allergen exposure in patients with asthma.…”
mentioning
confidence: 99%